Potential Oncogenic Effect of the MERTK-Dependent Apoptotic-Cell Clearance Pathway in Starry-Sky B-Cell Lymphoma - Farnworth-McHugh, Sarah; Barth, Nicole; Melville, Lynsey; Paterson, Margaret; Lynch, Catherine; Holland, Pamela; Dransfield, Ian; Gregory, Christopher (Frontiers in Immunology, 2020)
The histological architecture of certain aggressive B-cell lymphomas (prototypically Burkitt’s lymphoma, BL) is characterized by a “starry-sky” (SS) appearance. This is caused by tumor-associated macrophages (TAMs), which appear in standard histological preparations as “stars” in a darkly-stained “sky” of lymphoma cells. SS-TAMs accumulate in response to constitutive apoptosis in these tumors and are activated by the apoptotic tumor cells to a pro-oncogenic phenotype. The extent to which SS-TAMs contribute to lymphoma growth through responses generated by interactions with apoptotic tumor cells is unknown. Here we demonstrate a role for the receptor tyrosine kinase, MERTK, in the oncogenic activity of SS-TAMs. We show that MERTK expression is largely restricted to the macrophages of human BL and of murine models of SS B-cell lymphoma and that it is up-regulated in SS-TAMs as compared to germinal center or paracortical macrophages of normal lymph nodes. Our results further demonstrate that MERTK is active in the phagocytosis of apoptotic lymphoma cells by macrophages and, most significantly, that SS lymphoma growth is markedly inhibited in Mertk-/- mice. These results point toward the MERTK apoptotic-cell clearance/response pathway playing a key role in growth of aggressive B-cell lymphoma and identifies MERTK as a novel potential anti-lymphoma target.